The impact of prophylactic salpingo-oophorectomy on menopausal symptoms and sexual function in women who carry a BRCA mutation - Finch, A.; Metcalfe, K.A.; Chiang, J.K.; Elit, L.; McLaughlin, J.; Springate, C.; Demsky, R.; Murphy, J.; Rosen, B.; Narod, S.A. (Gynecologic oncology, 2011)
Prophylactic salpingo-oophorectomy is recommended to women who carry a BRCA1 or BRCA2 mutation to reduce the risks of breast, ovarian and fallopian tube cancer. We measured the impact of prophylactic salpingo-oophorectomy on menopausal symptoms and sexual functioning in women with a BRCA mutation. Women who underwent prophylactic salpingo-oophorectomy between October 1, 2002 and June 26, 2008 for a known BRCA1 or BRCA2 mutation were invited to participate. Participants completed questionnaires before prophylactic surgery and again one year after surgery. Measures of sexual functioning and menopausal symptoms before and after surgery were compared. Satisfaction with the decision to undergo prophylactic salpingo-oophorectomy was evaluated. 114 women who underwent prophylactic surgery completed questionnaires before and one year after surgery. Subjects who were premenopausal at the time of surgery (n=75) experienced a significant worsening of vasomotor symptoms (hot flashes, night sweats and sweating) and a decline in sexual functioning (desire, pleasure, discomfort and habit). The increase in vasomotor symptoms and the decline in sexual functioning were mitigated by HRT, but symptoms did not return to pre-surgical levels. HRT decreased vaginal dryness and dyspareunia; however, the decrease in sexual pleasure was not alleviated by HRT. Satisfaction with the decision to undergo prophylactic salpingo-oophorectomy remained high regardless of increased vasomotor symptoms and decreased sexual function. Women who undergo prophylactic salpingo-oophorectomy prior to menopause experience an increase in vasomotor symptoms and a decrease in sexual functioning. These symptoms are improved by HRT, but not to pre-surgical levels. ► Premenopausal women experienced increased vasomotor symptoms and decreased sexual function. ► HRT after surgery mitigated these symptoms but not to pre-surgery levels. ► The decrease in sexual pleasure was not alleviated by hormone replacement therapy.